Secondary data in mixed methods research - Watkins, Daphne (Mixed methods research series, 2023)
ith the increasing amount of secondary data available through journals and repositories, researchers have a trove of sources for investigations at their fingertips, but few books to guide them. This book provides readers with a step-by-step procedure for incorporating secondary data into various mixed methods research designs, as well as identifying key characteristics of existing datasets that make them good candidates for mixed methods projects and giving ideas for new uses of secondary data. Introductory chapters help the reader understand the "what" and "why" of secondary data. Subsequent chapters address the use of secondary data in convergent, exploratory sequential, explanatory sequential, and other complex research designs. The final chapters delve into writing and reporting on projects before, during, and after the project. Quotes throughout the chapter help readers remember key bits of knowledge, while learning objectives and summaries in each chapter structure the reading experience. Application questions at the end of each chapter help readers recall information and apply it to their own research projects. By emphasizing how to use existing qualitative and quantitative datasets in mixed methods research, this book will help readers answer new and ongoing questions in social science research. --